2022
DOI: 10.1111/odi.14455
|View full text |Cite
|
Sign up to set email alerts
|

Activated fibroblasts induce immune escape of TSCC through CCL25/AKT pathway

Abstract: ObjectivesAccumulating evidence suggests that activated fibroblasts are the key cells in the T‐cell response to tumor immunosuppression. We attempted to investigate the effect of activated fibroblasts on PD‐L1 expression and the related immune escape mechanism in tongue squamous cell carcinoma.MethodsWestern blotting, qPCR, and other techniques were used to study the expression of PD‐L1 in tongue squamous cell carcinoma cells and the nude mouse model of transplanted tumors in vivo; clinical tissue samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Through GSVA, we found that the genes in the high‐risk group were enriched mainly in angiogenesis, stromal cells, M2 macrophages, the extracellular matrix (ECM) and glucose metabolism. Stromal cells and M2 macrophages can achieve immunosuppression and immune escape through various mechanisms 39–41 . Elevated glucose metabolism promotes the proliferation of BC cells and induces BC recurrence and metastasis 42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through GSVA, we found that the genes in the high‐risk group were enriched mainly in angiogenesis, stromal cells, M2 macrophages, the extracellular matrix (ECM) and glucose metabolism. Stromal cells and M2 macrophages can achieve immunosuppression and immune escape through various mechanisms 39–41 . Elevated glucose metabolism promotes the proliferation of BC cells and induces BC recurrence and metastasis 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Stromal cells and M2 macrophages can achieve immunosuppression and immune escape through various mechanisms. [39][40][41] Elevated glucose metabolism promotes the proliferation of BC cells and induces BC recurrence and metastasis. 42,43 Dysregulation of the ECM can disrupt tissue homeostasis, which can facilitate the occurrence and progression of tumours.…”
Section: F I G U R Ementioning
confidence: 99%